Pengaruh Komitmen Organisasi, Motivasi Kerja dan Kepuasan Kerja Terhadap Kinerja Pegawai di Dinas Perindustrian dan Perdagangan Kota Batam - Adhiyasa, Rendy Dwi; Indrayani, Indrayani; W, Diana Titik (Universitas Batam, 2022)
This study aims to examine and analyze the effect of organizational commitment, work motivation and job satisfaction on the performance of the State Civil Apparatus (ASN) of the Batam City Industry and Trade Office. The results of this study testing the effect of organizational commitment on employee performance using the t test with a significant level of 0.05 obtained a p-value of 0.041 <0.05, then reject H_0. This shows that there is a positive and significant effect of organizational commitment on employee performance at the Batam City Industry and Trade Office. The results of the analysis using the t test obtained a p-value of 0.015 <0.05, so reject H_0. These results indicate that in this study work motivation has a positive and significant effect on employee performance in the Batam City Industry and Trade Office. The results of the job satisfaction test with the t test obtained a p-value of 0.000 <0.05, so rejecting H_0 can be said that there is a positive and significant effect of job satisfaction on employee performance in the Batam City Industry and Trade Service. This research is tested simultaneously using the F test with a significant level of 0.05 obtained a p-value of 0.000, so reject H_0. The results of this study indicate that the variables of organizational commitment, work motivation and job satisfaction together will affect employee performance.